Acute effects of combined isometric and plyometric conditioning activities on sports performance and tendon stiffness in female volleyball players - Kalinowski, Rafał; Pisz, Anna; Kolinger, Dominik; Wilk, Michał; Stastny, Petr; Krzysztofik, Michał (Frontiers in Physiology, 2022)
This study aimed to compare the effects of bilateral and unilateral conditioning activities (CA; combined isometric and plyometric) on countermovement jump performance, modified t-agility test, Achilles tendon stiffness and skin surface temperature. Thirteen female semi-professional volleyball players performed two CAs in random order: 1) bilateral isometric half back squats followed by bilateral drop jumps (BI-CA); and 2) unilateral isometric half back squats followed by unilateral drop jumps (UNI-CA). To assess the effects of CAs, countermovement jump, modified t-agility test, Achilles tendon stiffness and skin surface temperature measurements were performed 5 min before and 6 min after the CA. Both CAs significantly increased thigh skin surface temperature from pre- to post-CA (BI-CA, p < 0.001; effect size [ES] = 1.41 and UNI-CA, p = 0.001; ES = 1.39) but none of them influenced modified t-agility test time (interaction: p = 0.338, main effect of time: p = 0.121 and condition: p = 0.819). The countermovement jump height and modified reactive strength index significantly increased from pre-to post-CA during the BI-CA condition (p = 0.003, ES = 0.45, and p = 0.008, ES = 0.48) but not for UNI-CA (p = 0.061, ES = 0.18 and p = 0.065, ES = 0.26). No significant impact has been found for countermovement depth (interaction: p = 0.054, main effect of time: 0.097, and condition: p = 0.41) as well as for contraction time (interaction: p = 0.536, main effect of time: p = 0.224, and condition: p = 0.807). Moreover, stronger and weaker limb CMJ relative peak force significantly decreased from pre-to post-CA (p = 0.014, ES = −0.31, and p = 0.027, ES = −0.26; respectively) during UNI-CA condition but not for BI-CA (p = 0.096, ES = 0.23, and p = 1.41, ES = 0.18). The stronger and weaker limb Achilles tendon stiffness significantly increased from pre-to post-CA during the UNI-CA condition (p = 0.013, ES = 0.60 and p < 0.001, ES = 0.79; respectively) but not for BI-CA (p = 0.66; ES = 0.15 and p = 0.265; ES = 0.42). Furthermore, the post-CA stronger limb Achilles tendon stiffness during the UNI-CA was significantly higher than that noted during the BI-CA (p = 0.006, ES = 0.7). The present study showed that combined isometric and plyometric bilateral CA effectively improved the countermovement jump but did not enhance the t-agility test performance. These findings indicate that exercise combinations could effectively produce a post-activation performance enhancement effect but should replicate the following explosive task as much as possible.